Elimination of Building Tax in Indonesia - Usman, Agung Andrianto (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The abolition of property taxes as a fiscal policy is the subject of the normative legal examination referred to in this journal. Using a normative legal approach, this research examines the legal norms that apply in the context of eliminating land and building tax. Laws and regulations relating to property taxes, applicable legal concepts, and related court decisions are all identified and analyzed in this research. The authors take what they call a “normative legal approach,” which involves constructing arguments and judgments based on relevant legal law. Based on these findings, there are a number of legal considerations that need to be made before eliminating land and building taxes can be implemented as a fiscal strategy. The author here highlights legal concepts related to justice and legal certainty, as well as the ability of local governments to impose and eliminate land and building taxes. This study expands our knowledge of the statutory and constitutional issues surrounding the elimination of property taxes. The findings of this normative legal analysis can serve as a basis for developing policies that pay attention to the law, protect the rights of property owners, and advance the cause of justice and legal certainty